2017
DOI: 10.1186/s13741-017-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

American Society for Enhanced Recovery (ASER) and Perioperative Quality Initiative (POQI) joint consensus statement on optimal analgesia within an enhanced recovery pathway for colorectal surgery: part 1—from the preoperative period to PACU

Abstract: BackgroundWithin an enhanced recovery pathway (ERP), the approach to treating pain should be multifaceted and the goal should be to deliver “optimal analgesia,” which we define in this paper as a technique that optimizes patient comfort and facilitates functional recovery with the fewest medication side effects.MethodsWith input from a multi-disciplinary, international group of clinicians, and through a structured review of the literature and use of a modified Delphi method, we achieved consensus surrounding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 112 publications
0
75
0
2
Order By: Relevance
“…Although opiates still appear as a cornerstone in multiple analgesic regimens all around the world, their deleterious side effects in general, and specific to the surgical patient, have been well documented . Most successful enhanced recovery programs place a great emphasis on the ability to avoid opiates through a multimodal narcotic sparing approach.…”
Section: Multimodal Analgesia and Opiate Sparing Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although opiates still appear as a cornerstone in multiple analgesic regimens all around the world, their deleterious side effects in general, and specific to the surgical patient, have been well documented . Most successful enhanced recovery programs place a great emphasis on the ability to avoid opiates through a multimodal narcotic sparing approach.…”
Section: Multimodal Analgesia and Opiate Sparing Strategiesmentioning
confidence: 99%
“…By decreasing or eliminating opiates, dry mouth, dysphoria, and organ dysfunction (including ileus) can be attenuated, facilitating early feeding and ambulation. When optimized, narcotic‐sparing analgesia significantly accelerates functional recovery …”
Section: Multimodal Analgesia and Opiate Sparing Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies from countries including Taiwan, India, and the US have all consistently found that regional anesthesia-based approaches to operations as diverse as colorectal surgery, anterior cruciate ligament repair, total knee and hip arthroplasties, breast surgery, and carotid endarterectomy demonstrated faster recoveries, decreased side effects such as post-operative nausea, shorter hospital stays, and decreased overall costs when compared to general anesthesia and opioid-based approaches. 2329 Similarly, the public has great interest in containing the evolving disaster that is the US opioid epidemic. With approximately 10 million Americans reporting using opioids for non-medical reasons, nearly 2 million meeting substance abuse diagnostic criteria for opioids, and as many as 91 deaths every day due to opioid overdose, it is imperative that effective methods for opioid-sparing pain control be employed whenever possible.…”
Section: Stakeholdersmentioning
confidence: 99%